Implementasi Pedoman Umum Pembentukan Desa/Kelurahan Tangguh Bencana di Kabupaten Sigi - Afdal; Muh. irfan mufti; Hasan muhamad (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is to clearly understand the implementation of general guidelines for the formation of disaster resilient villages/subdistricts in Sigi Regency. The results of the research show that the implementation of general guidelines for the formation of disaster resilient villages/subdistricts in Sigi Regency. It is quite good, it can be seen from the fulfillment of aspects of policy standards and targets, communication between organizations that is quite good and social, political and economic conditions that support it well. Furthermore, the implementing resources are still not sufficiently well met in carrying out the disaster resilient village program both in quantity and quality, the pattern of division of work has not been implemented optimally and the attitude of the implementers in carrying out their duties and responsibilities has not been implemented well, only a few individuals are active in building collaborative relationships with external parties in a collaborative manner, all departments should contribute actively in accordance with their main duties and functions in realizing the formation of disaster resilient villages in the Sigi Regency area in accordance with the mandate of the law.